PREFERENSI KONSUMEN DALAM PEMBELIAN PRODUK TWISTPI KERIPIK BAYAM DI KOTA BOGOR MENGGUNAKAN MULTIFISHBEN - Rasidin Karo-Karo; Fauzaan Fadhlurrohman Madyananda; Nelson A Pane; Aisyah Rahma Putri; Zahra Qolbu Rasyid; Ainun Ratu Ajizah (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyze consumer preferences for Twistpi spinach chips in Bogor City using the Multiattribute Fishbein model. Methods: The research was conducted at the IPB Vocational School using purposive sampling with 100 respondents. Primary data were collected through surveys and questionnaires and analyzed based on six product attributes: taste, aroma, price, texture, packaging design, and color. Results: The results show that price (score 4.27) and texture (score 4.21) are the most important attributes for consumers. The highest belief score is also on price (4.34), followed by taste (4.25) and texture (4.24). The overall attitude score (Ao) indicates a